In vitro-in vivo Correlation for Poly (3-Hydroxybutyrate) Base Ibuprofen Extended Release Tablets - Payghan, Dr. Santosh Ambadas (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The aim of this study was to develop an in-vitro-in-vivo correlation (IVIVC) for two ibuprofen (IF) and extended release (ER) formulations and to compare their plasma concentrations. Materials and Methods: In vitro release rate data were obtained for each formulation using the USP apparatus 2, paddle stirrer at 100 rpm in pH 6.8 phosphate buffer. In vitro samples were analyzed using high performance liquid chromatography (HPLC) with ultraviolet detection, and in vivo samples were analyzed using a HPLC assay an additional model dependent approaches for different types of release rate of IF was prepared for evaluating the external predictability. Results and Discussion: A Higuchi model optimally fits the in vitro data. The similarity factor (f2) was used to analyze the dissolution data. In vivo plasma concentrations and pharmacokinetic parameters in New Zealand rabbits were obtained after administering oral, Poly-Î²-hydroxybutyrate, and hydroxypropyl methylcellulose base ER formulations. A linear correlation model was developed using percent absorbed data and percent dissolved data from the two formulations. Conclusion: Linear regression analyses of the mean percentage of dose absorbed versus the mean in vitro release resulted in a significant correlation (r2>0.95) for the two formulations.